Multi-Functional Lanthanide Metallopolymer Self-Healing and Photo-Stimuli-Responsive Dual-Emitting Luminescence for Diverse Applications - Zhao, Di (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.